Validation of a point-of-care instrument for bedside glutamine screening in the intensive care unit. Issue 1 (February 2017) - Pettersson, Linn; Rydén, Sara; Smedberg, Marie; Tjäder, Inga; Rooyackers, Olav; Wernerman, Jan
Summary: Background: A point-of-care instrument developed for measuring glutamine levels in cell cultures was validated for bedside use in the ICU setting and compared with a standard HPLC technique to measure plasma glutamine. The aim was to evaluate the instrument for absolute measurements and for screening purposes. Methods: Consecutive blood samples were obtained from one hundred adult ICU patients 3–5 days apart during their ICU stay. Each sample was divided into 3 aliquots, out of which two were used for analyses of plasma and whole blood glutamine by the point-of-care instrument, and one was used for analysis of plasma glutamine concentration by the gold standard HPLC technique. Comparisons were performed by Bland–Altman analyses. Results: Comparison of the initial plasma sample of each subject (n = 100), between the point of care instrument and HPLC analysis revealed a systematic bias of −221 μmol/L. Comparisons between plasma and whole blood on the point-of-care instrument revealed comparable results. After pragmatic adjustments for the measured bias and hematocrit, whole blood analyses during ICU stay (n = 316) compared with HPLC plasma analyses showed a line of identity of −34 μmol/L and limits of agreement between 288 and -355 μmol/L. Conclusion: When compared to the HPLC gold standard in particular, the lines of agreement indicate that the point-of-care instrument is not suitable for quantitative plasma or whole blood glutamine concentration measurements. For screening purposes the instrument may be useful in order to identify patients with hypoglutaminemia and hyperglutaminemia and the tested accuracy was high enough for safe supplementation of glutamine to patients with low plasma values measured with the device. The point-of-care instrument may also serve as a screening tool for scientific studies.